Ku-Band Low Noise Block Converter (LNB) Sync Application Design Using Android Based Solid Dish - Junaidi Salat; Cut Lilis Setiawati; Zikrul Khalid (Budapest International Research and Critics University, 2021)
Mobile phone users, especially the Android version of the smartphone, are increasingly spoiling their users. It is undeniable that users do not know their age, even many children have an Android version of the smartphone to play with. Meanwhile, in the satellite tracking world, the satellite tracking is still using TV when tracking the satellite so that it feels difficult. ApplicationLow Noise Block Converter is a video view application from a receiver to an Android smartphone that was built to make it easier for tracking satellites to track one of the satellites that you want to lock. This application also includes satellite tracking information facilities such as tracking guides, frequency updates, and satellite location. ApplicationLow Noise Block Converterbuilt with the Android Studio application using the Java programming language. With the creation of the applicationLow Noise Block Converter seas a new alternative to replace TV as a satellite tracking device or monitoring tool.